Body, Possibility and Biographical Interpretation - Pereira, Anabela (Qualitative Sociology Review, 2012)
The aim of this article is to demonstrate how body-representations offer an opportunity for its visual interpretation from a biographical point of view, enhancing, on the one hand, the image’s own narrative dynamics, and, on the other, the role of the body as a place of incorporation of experiences, as well as, a vehicle mediating the individual interaction with the world. Perspective founded in the works of the artists Helena Almeida and Jorge Molder, who use self-representation as an expression of these incorporated (lived) experiences, constitutes an important discursive construction and structuring of their narrative identity through visual creation, the artists enable the other with moments of sharing knowledge, creativity and subjectivity, contributing also to the construction of the contemporary, cultural and social imagery.